Predation and parasitism of Cirrospilus neotropicus (Hymenoptera: Eulophidae) on Phyllocnistis citrella (Lepidoptera: Gracillariidae) in laboratory - FOELKEL, ESTER; RODRIGUES-REDAELLI, LUIZA; MUNDSTOCK-JAHNKE, SIMONE; BAERLE LOSEKANN, PAULA (Revista Colombiana de Entomología, 2009)
The predation and parasitism of Cirrospilus neotropicus (Hymenoptera: Eulophidae) was evaluated on third instar Phyllocnistis citrella (Lepidoptera: Gracillariidae) larvae reared on Citrus limonia under controlled conditions (25 ± 1ºC; L:D 12:12 h). Two groups of parasitoid females were evaluated: one in which pupae were collected from citrus orchards (field females) at Eldorado do Sul, RS, Brazil (30°29’S, 51°06’W), and the other from a laboratory colony (laboratory females). After mating, each female was maintained in an individual container and fed honey, pollen and 12 P. citrella every 48 hours. In both groups the behaviors of predation (host feeding), oviposition and superparasitism were observed. The average percent mortality caused by field females (48.71 ± 3.29%) was significantly higher than that caused by laboratory females (35.12 ± 3.45%)(H = 4.74; P = 0.01). Mortality due to predation was 19.15 ± 1.75% in field females and 25.11 ± 3.82% in laboratory females, with no significant difference (H = 1.57; P = 0.21). The average percent parasitism without predation did not differ significantly between field (49.15 ± 2.89%) and laboratory females (42.33 ± 4.07%)(H = 0.53; P = 0.47). Superparasitism represented 6.92 ± 1.21% of the total hosts killed by field females, and 3.51 ± 0.99% by laboratory females. The results show the influence of P. citrella in the death of C. neotropicus caused by parasitism and predation.